Análisis de estabilidad de un talud en centrifuga geotécnica (2019)
This is a document that studies the stability of slopes, it describes the physical modeling in the geotechnical centrifuge, through which, we want to study the response of a clayey soil to two alternatives for stabilization, the nails and micropiles, the process used for each prototype is described in a general way and the methodology used is based on the basic concepts of an undrained condition of the slope. To analyze the modeled prototypes were used an analytical method and finite element software. Subsequently, the safety factors for each modeled prototype were compared.